State of the art and future directions in assessing the quality of life in rare and complex connective tissue and musculoskeletal diseases - Trieste, Leopoldo; Cannizzo, Sara; Palla, Ilaria; Triulzi, Isotta; Turchetti, Giuseppe (Frontiers in Medicine, 2022)
Background As chronic conditions, rare and complex connective tissue and musculoskeletal diseases (rCTDs) significantly affect the quality of life generating an impact on the physical, psychological, social, and economic dimensions of the patients’ lives, having implications on the family, changing the lifestyle and interpersonal relationships. Traditionally, generic and disease-specific measures for Quality of Life (QoL) provide valuable information to clinicians since QoL affects healthcare services utilization, predicts morbidities and mortalities, workability, etc. Moreover, the assessment of unmet clinical needs, satisfaction, the experience with the treatment and the care, the psychological dimensions, and the effects of the diseases, such as fatigue, could represent valuable dimensions to be considered in the QoL impact assessment. It is also necessary to measure the impact of rCTDs by considering the perspectives of family members/informal caregivers, for instance considering values, beliefs, experiences, life circumstances, psychological aspects, family relationships, economic issues, changes in social activities, etc. Objective The aim of this scoping review is to better understand the status of QoL metrics used in clinical and economic research for the assessment of the individual’s perspective on living with rCTDs. Research question What are the main challenges in QoL measures (and/or) measurement/assessment in rCTDs? Materials and methods Scoping review of the literature referring to QoL measures in rCTDs. Database: PUBMED, ISI-Web of Science; last date: 21/09/2021. Results Anxiety and depression, body image satisfaction, daily activity, fatigue, illness perception, pain, personality, QoL, resilience, satisfaction with the relationship, self-management, sexual QoL, sleep quality, social support, stress, uncertainty, and work productivity are the observed dimensions covered by the included studies. However, “more shadows than lights” can summarize the review’s outcome in terms of Patient Reported Outcome Measures (PROMs) domains covered for each of the rCTDs. Also, for those diseases characterized by a relatively high prevalence and incidence, such as Systemic Lupus Erythematosus, Sjögren’s Syndrome, and Systemic Sclerosis, the analysis of patients’ resilience, satisfaction with the quality of the relationship, personality, and stress are still missing dimensions. It has been observed how reducing items, increasing the number of domains, and disease-specific questionnaires characterize the “technological trajectory,” such as the evolution of questionnaires’ characteristics for assessing QoL and QoL-related dimensions and the burden of rCTDs. Conclusion The scoping review presents an overview of studies focused on questionnaires used to evaluate the different dimensions of quality of life in terms of general instruments and disease-specific questionnaires. Future research should include the co-design with patients, caregivers, and patient representatives to create questionnaires focused on the unmet needs of people living with rCTDs.